On social and psychological aspects of a negligible reception of Natanson’s article of 1911 in the early history of quantum statistics - Nobukata Nagasawa (Studia Historiae Scientiarum)
Possible reasons are studied why Ladislas (Władysław) Natanson’s paper on the statistical theory of radiation, published in 1911 both in English and in the German translation, was not cited properly in the early history of quantum statistics by outstanding scientists, such as Arnold Sommerfeld, Paul Ehrenfest, Satyendra Nath Bose and Albert Einstein.